STATE OF POLITICAL SCIENCE AT KHARKOV UNIVERSITY IN THE LATE XIX - EARLY XX CENTURY - Пересада, О.О. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science")
This article is focused on the University politcal science status at the end of XIX - early XX century. It ’s noticed the complexity of thepolitical science study in this period. Some scientists, who worked during this period are being analyzed. There are still gaps in literature which is devoted to this topic reserach which remains particulary relevant . It is also important to build compete picture of political science contemplation of that period.